2003
DOI: 10.1086/376964
|View full text |Cite
|
Sign up to set email alerts
|

The Redshift and the Host Galaxy of GRB 980613: A Gamma-Ray Burst from a Merger-induced Starburst?

Abstract: We present the optical and near-IR identification and spectroscopy of the host galaxy of gamma-ray burst GRB 980613. The burst was apparently associated with the optically (rest-frame UV) brightest component of an apparent system of at least five galaxies or galaxy fragments, at least two of which are at a redshift of . The z p 1.0969 component we identify as the host galaxy shows a moderately high unobscured star formation rate, SFR ∼ 5 M , yr , but a high SFR per unit mass, indicative of a starburst. The ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…One immediately sees from Table 4 that the SFRs of the hosts are moderate, in line with the conclusions of Fruchter et al (1999a); Djorgovski et al (2003Djorgovski et al ( , 2001a; Castro-Tirado et al (2001). In Fig.…”
Section: Star-formation Ratessupporting
confidence: 83%
“…One immediately sees from Table 4 that the SFRs of the hosts are moderate, in line with the conclusions of Fruchter et al (1999a); Djorgovski et al (2003Djorgovski et al ( , 2001a; Castro-Tirado et al (2001). In Fig.…”
Section: Star-formation Ratessupporting
confidence: 83%
“…When is reported in the literature but is not, we set ¼ À1 (marked with an asterisk; see Appendix A). When multiple references are available (i.e., Jimenez et al 2001;Amati et al 2002; Kulkarni et al 1998;(9) Bloom et al 1999;(10) Groot et al 1998;(11) Lamb et al 1999;(12) Yost et al 2002;(13) Tinney et al 1998;(14) Jaunsen et al 2001;(15) Djorgovski et al 2003;(16) Halpern & Fesen 1998;(17) Djorgovski et al 1998;(18) Frail et al 2003;(19) Frontera et al 2000;(20) Frail et al 1999;(21) Kulkarni et al 1999;(22) Bloom et al 2003a;(23) Vreeswijk et al 2001;(24) Stanek et al 1999;(25) (26) Le Floc'h et al 2002;(27) Masetti et al 2000;(28) Frontera et al 2001;(29) Björnsson et al 2001;(30) Djorgovski et al 1999a;(31) Hurley et al 2000b;(32) Sagar et al 2000;(33) Djo...…”
Section: 3mentioning
confidence: 99%
“…From an analysis of photometric redshifts of galaxies in the field of GRB 000210, Gorosabel et al (2003) found that there is no obvious concentration of galaxies around the host. In another case, the afterglow of GRB 980613 was located close to a very compact object inside a complex region consisting of star forming knots and/or interacting galaxy fragments Djorgovski et al 2003). If these host galaxies are associated with the underlying large-scale structure of the universe, then they should show galaxy clustering properties similar to normal galaxies.…”
Section: Introductionmentioning
confidence: 99%